Optimal selling time in livestock production - Torres Carbonell, Carlos Alberto (2025)
Purpose: This paper analyzes the application of real options to livestock production. It evaluates the strategic flexibility in determining the optimal selling time for livestock, considering the technological and market risks involved in its production. Design/methodology/approach: Based on a data sample of 300 records collected over the past 15 years, a biophysical-economic model was developed and simulated using an iterative stochastic procedure. Findings: The alternatives that provide the highest profit growth are identified by quantifying their risk parameters and yielding strategies for enhancing the value of livestock companies. Originality/value: This research aims to understand how to improve decision-making in companies managing biological assets under conditions of risk and uncertainty, using the case of livestock systems in Argentina as a basis. This case can be easily adapted to similar cases in other countries.